The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1021/jo00345a025
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bromination of uracil derivatives. 6. Cytosine and N-substituted derivatives

Abstract: temperature and then acidified with dilute HC1 while cooling. The initial red color turned to yellow and then white. After the mixture was cooled in ice, a solid precipitate was collected, washed with H20, and dried under vacuum (0.1 mm). Taken up in 2 L of boiling CH3CN containing Norit, filtered, concentrated to 1 L, and cooled, it gave a first crop, and after concentration to 250 mL, a second was obtained for a total yield of tetranitrile 2 amounting to 3.15 g (81%): mp 325-330 °C dec (lit.2 mp >360 °C);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Where does BrU come from? Early studies have shown that Br 2 /H 2 O or hypobromous acid (HOBr) can oxidize uracil into BrU. , Furthermore, eosinophils could use eosinophil peroxidase, hydrogen peroxide (H 2 O 2 ), and bromide ion (Br - ) to generate HBrO. , HOBr generated by eosinophil peroxidase might brominate uracil to BrU. A similar phenomenon was also observed when myeloperoxidase, hydrogen peroxide, and bromine system coexisted with uracil. , …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Where does BrU come from? Early studies have shown that Br 2 /H 2 O or hypobromous acid (HOBr) can oxidize uracil into BrU. , Furthermore, eosinophils could use eosinophil peroxidase, hydrogen peroxide (H 2 O 2 ), and bromide ion (Br - ) to generate HBrO. , HOBr generated by eosinophil peroxidase might brominate uracil to BrU. A similar phenomenon was also observed when myeloperoxidase, hydrogen peroxide, and bromine system coexisted with uracil. , …”
Section: Introductionmentioning
confidence: 94%
“…Early studies have shown that Br 2 /H 2 O or hypobromous acid (HOBr) can oxidize uracil into BrU. 19,20 Furthermore, eosinophils could use eosinophil peroxidase, hydrogen peroxide (H 2 O 2 ), and bromide ion (Br -) to generate HBrO. 21,22 HOBr generated by eosinophil peroxidase might brominate uracil to BrU.…”
mentioning
confidence: 99%
“…Derivatives of uracil were reported to react with electrophilic reagents not only at both nitrogen atoms (or at the oxygen atoms), [8][9][10][11] but also at the C-5 or C-6 carbon atoms. 12,13 Regioselectivity and poly-alkylation reactions complicate the alkylation reaction 10,11,14 of derivatives of nucleic acid bases.…”
Section: Methodsmentioning
confidence: 99%